KEVALIDAN DAN KEPRAKTISAN MEDIA PEMBELAJARAN GALERI PUISI BERBANTUAN GOOGLE SITES PADA MATERI TEKS PUISI SISWA KELAS VIII SMP NEGERI 4 TANJUNGPINANG - Francisca Br Hutasoit, Juliana; Elfitra, Legi; Ariance Loren, Fabio Testy; Elfiza, Rona; Lolita, Asri; Andheska, Harry; Wahyusari, Ahada; Irawan , Dody (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to develop an instructional medium in the form of a Poetry Gallery utilizing the Google Sites platform for teaching poetry texts to eighth-grade students at SMP Negeri 4 Tanjungpinang. The primary focus of this development is to assess the validity and practicality of the designed media. The development model employed is based on the 4D model, which was modified into three stages: define, design, and develop. The learning media developed is an interactive digital platform consisting of four main components: learning outcomes, learning objectives, material content, and quizzes. The validation process was conducted by two experts, namely a media expert and a content expert. To evaluate the practicality of the media, trials were conducted with two groups of students: a small group of 8 students and a large group of 40 students. Data were collected using two approaches: qualitative descriptive methods to analyze feedback, suggestions, and comments on the media, and quantitative descriptive methods to assess the scores related to the media’s validity and practicality. The validation results indicated that the media achieved a validity score of 88%, categorized as “valid and practical,” while the material validation reached 82%, categorized as “highly valid and highly practical.” The practicality tests conducted with students showed a score of 84% in the small group and 83% in the large group, which are classified as “highly practical and valid” and “practical and valid,” respectively.